On the relation between apparent ion and total particle growth rates in the boreal forest and related chamber experiments - L. Gonzalez Carracedo; K. Lehtipalo; K. Lehtipalo; L. R. Ahonen; N. Sarnela; S. Holm; J. Kangasluoma; M. Kulmala; M. Kulmala; M. Kulmala; M. Kulmala; P. M. Winkler; et al. (Atmospheric Chemistry and Physics, 2022)
The understanding of new particle formation and growth processes is critical for evaluating the role of aerosols in climate change. One of the knowledge gaps is the ion–particle interaction during the early growth process, especially in the sub-3 nm range, where direct observations are sparse. While molecular interactions would imply faster growth rates of ions compared to neutral particles, this phenomenon is not widely observed in the atmosphere. Here, we show field measurements in the boreal forest indicating a smaller apparent growth rate of the ion population compared to the total particles. We use aerosol dynamics simulations to demonstrate that this effect can be caused by the changing importance of ion-induced nucleation mechanisms during the day. We further compare these results with chamber experiments under similar conditions, where we demonstrate that this effect critically depends on the abundance of condensable vapors and the related strength of ion-induced nucleation. Our results imply that atmospheric ion growth rate measurements below 3 nm need to be evaluated very carefully as they do not represent condensational growth alone but are influenced by ion–particle population interactions.